Inflammation-induced lysosomal dysfunction in human iPSC-derived microglia is exacerbated by APOE 4/4 genotype - Marianna Hellén; Isabelle Weert; Stephan A. Müller; Noora Räsänen; Pinja Kettunen; Šárka Lehtonen; Michael Peitz; Klaus Fließbach; Mari Takalo; Marja Koskuvi; Stefan F. Lichtenthaler; Ville Leinonen; et al. (Journal of Neuroinflammation)
Abstract Background The ε4 isoform of apolipoprotein E (ApoE) is the most significant genetic risk factor for Alzheimer’s disease. Glial cells are the main source of ApoE in the brain, and in microglia, the ε4 isoform of ApoE has been shown to impair mitochondrial metabolism and the uptake of lipids and Aβ42. However, whether the ε4 isoform alters autophagy or lysosomal activity in microglia in basal and inflammatory conditions is unknown. Methods Altogether, microglia-like cells (iMGs) from eight APOE3/3 and six APOE4/4 human induced pluripotent stem cell (iPSC) lines were used in this study. The responses of iMGs to Aβ42, LPS and IFNγ were studied by metabolomics, proteomics, and functional assays. Results Here, we demonstrate that iMGs with the APOE4/4 genotype exhibit reduced basal pinocytosis levels compared to APOE3/3 iMGs. Inflammatory stimulation with a combination of LPS and IFNγ or Aβ42 induced PI3K/AKT/mTORC signaling pathway, increased pinocytosis, and blocked autophagic flux, leading to the accumulation of sequestosome 1 (p62) in both APOE4/4 and APOE3/3 iMGs. Exposure to Aβ42 furthermore caused lysosomal membrane permeabilization, which was significantly stronger in APOE4/4 iMGs and positively correlated with the secretion of the proinflammatory chemokine IL-8. Metabolomics analysis indicated a dysregulation in amino acid metabolism, primarily L-glutamine, in APOE4/4 iMGs. Conclusions Overall, our results suggest that inflammation-induced metabolic reprogramming places lysosomes under substantial stress. Lysosomal stress is more detrimental in APOE4/4 microglia, which exhibit endo-lysosomal defects.